Failure of syndromic management due to drug-resistant Mycoplasma genitalium infection in South Africa: a case report. (April 2019) - Maduna, Liteboho D; Laumen, Jolein GE; Radebe, Oscar; Kock, Marleen M; Peters, Remco PH
We report a case of management failure of male urethritis syndrome due to macrolide-resistant Mycoplasma genitalium in South Africa. We detected mutations in 23S rRNA and one of the quinolone resistance-determining regions. This report confirms that drug-resistant M. genitalium infection can undermine the effectiveness of syndromic management in Africa.